PENATAAN KEPEMILIKAN TANAH PERTANIAN SECARA ABSENTEE MELALUI PROGRAM KARTU TANDA PENDUDUK ELETRONIK (KTP-EL) - Asri Alvionita, Ni Made; Utama, I Made Arya; Cakabawa Landra, Putu Tuni (Acta Comitas, 2018)
Absentee agricultural land ownership is caused by a void of norm in Article 3 PP No.224 of 1961. In the article is not expressly regulated on the requirements of a person can have agricultural land in the district of his residence. In addition, in Article 3 of PP No.224 of 1961 this does not set the requirements what is required to determine the truth of one's domicile. This creates a loophole for the smuggling of the law in order for a person to have absentee farmland. The provision has not been amended until now. Many of the fraud that arose in the implementation of the provisions on the prohibition of ownership of agricultural land in absentee is due to the existence of a vacuum norm in the article. The birth of the Electronic Identity Card Program, is a solution to prevent the absentee ownership of agricultural land. This study uses normative legal research that departs from the existence of a vacuum of norms related to the arrangement the prohibition of agricultural land ownership in absentee after the enactment of KTP-el that is in Article 3 PP No.224 of 1961. In that article is not regulated explicitly about the requirements of a person Can have farmland in the subdistrict of his residence area, causing a loophole for the smuggling of the law in order for a person to have absentee farmland. The result of this research is KTP-el serves as prevention of absentee farm land ownership. KTP-el will facilitate the task of a Notary in ensuring the truth of the identity of the parties facing to carry out the sale, especially in the case of the sale of agricultural land. Notary / PPAT in performing their duties, the Notary shall act in a trustworthy, honest, thorough, independent, impartial manner, and safeguard the interests of the parties concerned in a legal act. Notary / PPAT is required to carefully determine whether the parties to him can indeed carry out the process of buying and selling agricultural land. With the KTP-el, the Notary / PPAT will not hesitate to carry out the process of buying and selling agricultural land, when the buyer's domicile is in accordance with what is required by the law in Article 10 of UUPA, Article 3 paragraph (1) PP No.224 of 1961, and Article 3 of PP No.224 of 1961.   Keyword : ownership, agricultural land, electronik identity card